Deadly ethnic Riot - Horowitz, Donald L (New Delhi University Press, 2002)
This book examines approximately 150 such riots across fifty countries, mainly in Asia, Africa, and the former Soviet Union, as well as fifty control cases. Furious and sadistic, the riot is directed against a precisely specified class of targets and cond
Keywords: Ethnic groups